2009
DOI: 10.1111/j.1447-0756.2009.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of clomiphene citrate‐related ovarian cysts in a prospective randomized study. A single center experience

Abstract: Any treatment might be appropriate for patients with a CC-related ovarian cyst. However, there is no evidence to administer OC for treating CC-related ovarian cysts. Expectant management may also achieve similar success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Functional ovarian cysts have often been observed after ovulation induction. 10 High order multiple pregnancy rates are also found to be increased due to CC treatment. Moreover, ovarian hyperstimulation syndrome is a potentially serious complication of ovulation induction.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Functional ovarian cysts have often been observed after ovulation induction. 10 High order multiple pregnancy rates are also found to be increased due to CC treatment. Moreover, ovarian hyperstimulation syndrome is a potentially serious complication of ovulation induction.…”
mentioning
confidence: 78%
“…Functional ovarian cysts, ovarian hyperstimulation syndrome, and thinning of the endometrium are some of them. 10,11,24 In recent years, fears of cancer possibility induced by ovulation inducing agents have been raised and addressed by various study reports. 25 Among ovulation inducing agents, CC has been implicated in the etiology of genital organ cancers and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…9 Combined oral contraceptives (COCs) are frequently prescribed to women with ovarian cysts. Multiple randomized controlled trials have been performed and demonstrated that COCs do not expedite cyst resolution [10][11][12][13][14][15] ; however, COCs may prevent additional functional cysts from developing. Current evidence does not support COC administration for treatment of functional cysts.…”
Section: Managementmentioning
confidence: 99%